ESKALASI KONFLIK KELUARGA POLIGAMI DALAM DINAMIKA KETAHANAN KELUARGA: PAPARAN VISIONER REGULASI POLIGAMI BERDASARKAN PERGUB POLIGAMI ASN JAKARTA NOMOR 2 TAHUN 2025 TENTANG TATA CARA PEMBERIAN IZIN PERKAWINAN DAN PERCERAIAN - AGUS HARIATI, NINA (Institut Agama Islam Hasanuddin Pare, 2025)
DKI Jakarta Governor Regulation Number 2 of 2025 concerning Procedures for Issuing Marriage and Divorce Licenses has sparked controversy in society, particularly in the context of the political policies of the State Civil Apparatus (ASN). Although the purpose of this regulation is to provide legal guidance and regulate the practice of polygamy to be more controlled, it has still received criticism for not addressing the interests of women and children. Therefore, the purpose of this study is to analyze Governor Regulation Number 2 of 2025 concerning Procedures for Issuing Marriage and Divorce Licenses from the perspective of legal certainty to determine whether this regulation is in accordance with applicable legal principles. This study uses a normative juridical method with a descriptive analytical approach. A literature review was conducted to examine relevant laws and regulations, legal doctrine, and legal frameworks. Furthermore, a comparative study of regulations was conducted to understand the policy's implications for individual rights and legal compliance. The study findings indicate that while this law is intended to provide clearer legal guidance to Civil Servants (ASN), its implementation has the potential to increase tensions in marital relationships. Existing requirements do not guarantee fairness for wives and children, nor do they create room for discretion. Therefore, a review of this law is necessary to strengthen the protection of women's and children's rights and to utilize the law more comprehensively.